INDEKS MASSA TUBUH DENGAN KETIDAKTERATURAN SIKLUS MENSTRUASI PADA WANITA USIA SUBUR DI KECAMATAN LEIHITU BARAT - Frandita Ivana Tanisiwa; Seimahuira Theresia; Soumena Rifah (PAMERI, 2019)
Menstrual disorders are a fairly common problem in primary health care. According to World Health Organization (WHO) data in 2010, there are 75% of adolescents who experience menstrual disorders. Menstrual cycle disorders in women is one factor can occur infertility in women.This study aims to determine the relationship between body mass index and menstrual cycle in women of reproductiveage in West Leihitu District Central Maluku Regency.The research was an analytical descriptive study using cross sectional technique. Variables were age, height, weight, irregularity of menstrual cycle. This study uses primary data directly from the respondents. Data were analyzed using SPSS version 24.0. Based on the results of the study, the most age group was 18 years old (54.0%), the most body mass index was the normal weight group (41.0%), and the irregular menstrual cycle group (46.0%) Is the largest group. The result of bivariate analysis showed a significant correlation between body mass index and irregularity of menstrual cycle in women of reproductive age in West Leihitu District (p= 0.000).